Phát biểu khai mạc kỳ họp thứ 3, Quốc hội khóa XIV của Chủ tịch Quốc hội Nguyễn Thị Kim Ngân - Nguyễn Thị Kim Ngân (2017)
Phát biểu khai mạc kỳ họp thứ 3, Quốc hội khóa XIV của Chủ tịch Quốc hội Nguyễn Thị Kim Ngân ngày 22/05/2017.